Relationship between Perception of Oral Health, Clinical Conditions and Socio-Behavioral Factors of Mother-Child - Rocha, Najara Barbosa [UNESP]; Saliba Moimaz, Suzely Adas [UNESP]; Isper Garbin, Artenio Jose [UNESP]; Saliba, Orlando [UNESP]; Saliba Garbin, Clea Adas [UNESP] (Assoc Apoio Pesquisa & Saude Bucal-apesb, 2015)
Objective: To verify a mother's perception about her and her child's oral health as well as to analyze its association with socio-behavioral factors. Material and Methods: The study was conducted with 73 pairs of mother and child, through interviews, using a semi-structured questionnaire and clinical exam. The clinical variables studied were: caries prevalence and gingival diseases and nonclinical variables: socio-behavioral factors, perception and habits. Bivariate analyzes, logistic regression and odds ratio (p <= 0.05 and 95% CI) were employed. Results: Most mothers considered their oral health as poor (57.5%) and their children as good (68.5%). In the multivariate analysis, measures of self-perception of oral health were significantly associated with the presence of caries in the mother (p < 0.01), and oral health perception of the child was related to the presence of caries (p < 0.01) and marital status (0.05). Conclusion: The clinical and behavioral factors were associated with the measures of perceived oral health.
Keywords: Dental Caries; Oral Health; Risk Factors; Socioeconomic Factors